The Ministry of Industry, Trade and Small & Medium Projects Decree No. 853 of the Year 2014 = وزارة الصناعة والتجارة والمشروعات الصغيرة والمتوسطة قرار رقم 853 لسنة 2014 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic